Anatomy of the Islam Nusantara Program and the Necessity for a “Critical” Islam Nusantara Study - Okamoto Masaaki (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2020)
This paper analyzes the Islam Nusantara program of the Islamic Studies Institute of Nahdlatul Ulama (STAINU) and then of the Nahdlatul Ulama University of Indonesia (UNUSIA) that started in 2013. The largest Islamic social organization, Nahdlatul Ulama (NU) has emphasized the moderateness and tolerance of Islam in Indonesia and conceptualized its Islam as Islam Nusantara and started to disseminate this concept to stem the deepening conservative turn of Islam especially after the democratization in 1998. In order to disseminate Islam Nusantara more effectively, the NU-affiliated college (STAINU), later its university (UNUSIA) started the graduate program for Islam Nusantara. After elucidating the Islamic conservative turn and the propagation of Islam Nusantara both by NU and the state, this paper analyzes the theses and their abstracts and the biodata of authors of theses and sees how Islam Nusantara has been producing the proponents of Islam Nusantara. The paper finds that the authors of the theses are young and many of the theses analyze the harmonious Islamic adaptation to local cultures. The authors are male dominant and Java-born-dominant with the focus on their own birthplace. The paper concludes with the importance of more comparativeand critical analysis on local variations of Islam Nusantara in the future theses and dissertations so that the program can critically and objectively analyze the Islam Nusantara concept itself. Keyword: Islam Nusantara, Nahdlatul Ulama, UNUSIA Jakarta REFERENCE: Abdul Mun’im DZ. Mengukuhkan Jangkar Islam Nusantara, Tashwirul Afkar no.26, 2008. Abdurrahman Wahid. “Pribumisasi Islam.” Dalam Muntaha Azhari and Abdul Mun’im Saleh, eds. Islam Indonesia Menatap Masa Depan. Jakarta: P3M, 1989. Abdurrahman Wahid. “Melindungi dan Menyantuni Semua Paham.” Dalam Yenny Zannuba Wahid, Ahmad Suaedy et al., eds. Ragam Ekspresi Islam Nusantara. Jakarta: The Wahid Institute, 2008: h. xi-xii. Ahmad Najib Burhani. Islam Nusantara as a Promising Response to Religious Intolerance and Radicalism, Trends in Southeast Asia, 2018. No.21. Ahmad Suaedy. Islam, Minorities and Identity in Southeast Asia. Yogyakarta and Jakarta: inklusif and ISAIs UIN Yogya, 2018. Akhmad Sahal. “Prolog: Kenapa Islam Nusantara?” Dalam Akhmad Sahal dan Munawir Aziz eds. Islam Nusantara dari Ushul Fiqh hingga Paham Kebangsaan. Bandung: Mizan Pustaka, 2015. Akhmad Sahal dan Munawir Aziz eds. Islam Nusantara dari Ushul Fiqh hingga Paham Kebangsaan. Bandung: Mizan Pustaka, 2015. Anderson, Benedict. A Life Beyond Boundaries. Petaling Jaya: Strategic Information and Research Development Centre, 2016. Azymardi Azra. Islam Nusantara: Jaringan Global dan Lokal. Bandung: Mizan, 2002. Dawam Multazam. “Islam Nusantara, Dari NU untuk Dunia” (artikel diakses pada 10 January 2015 dari http://www.nu.or.id/post/read/60706/islam-nusantara-dari-nu-untuk-dunia). Fealy, Greg. “Nahdlatul Ulama and the Politics Trap.” New Mandala. (diakses pada 12 November 2019 pada https://www.newmandala.org/nahdlatul-ulama-politics-trap/), 2018. Fogg, Kavin W. “The Fate of Muslim Nationalism in Independent Indonesia.” PhD dissertation (Yale University), 2012. Formichi, Chiara. Islam and the Making of the Nation: Kartosuwiryo and Political Islam in 20th Century Indonesia. Leiden and Manoa: KITLV and Hawai’i University Press, 2011. Hefner, Robert W. “Islamic Schools, Social Movements, and Democracy in Indonesia.” Dalam Robert W. Hefner ed. Making Modern Muslim: the Politics of Islamic Education in Southeast Asia. Honolulu: University of Hawai’i Press, 2009: h. 55-105. Hefner, Robert. W. What Happened to Civil Islam? Islam and Democratisation in Indonesia, 20 Years On. Asian Studies Review. Vol.43. No.3, 2019: h. 375-396. Hoesterey, James Bourk. Public Diplomacy and the Global Dissemination of “Moderate Islam” Dalam Robert W. Hefner ed. Routledge Handbook of Contemporary Indonesia. London: Routledge, 2018: h. 406-416. IPAC (Institute for Policy Analysis of Conflict). After Ahok: The Islamist Agenda in Indonesia. IPCA Report No.44, 2018. Jadul Maula. Orientasi “Islam Nusantara”: Melahirkan “Insan (Kamil) Nusantara”. Tashwirul Afkar No. 13, 2006. Laffan, Michael, The Makings of Indonesian Islam: Orientalism and the Narration of a Sufi Past. New Jersey: Princeton University Press, 2011. Menchik, Jeremy. Islam and Democracy in Indonesia: Tolerance without Liberalism. Cambridge: Cambridge University Press, 2015. Nor Huda. Islam Nusantara: Sejarah Sosial Intelektual Islam di Indonesia. Yogyakarta: Ar-Ruzz Media, 2008. Pepinsky, Thomas B., Liddle, William R. and Saiful Mujani. Piety and Public Opinion: Understanding Indonesian Islam. Oxford: Oxford University Press, 2018. Power, Thomas P. Jokowi’s Authoritarian Turn and Indonesia’s Democratic Decline. Bulletin of Indonesian Economic Studies 53(3), 2018: h. 307-338. Robison, Richard and Hadiz, Vedi R. Reorganizing Power in Indonesia: The Politics of Oligarchy in An Age of Markets．London and New York: Routledge Curzon, 2004. Yenny Zannuba Wahid, Ahmad Suaedy et al. eds. Ragam Ekspresi Islam Nusantara. Jakarta: The Wahid Institute, 2015. Syafiq Hasyim. Islam Nusantara dalam Konteks: Dari Multikultralisma hingga Radkikalisme. Yogyakarta: Gading, 2018. van Bruinessen, Martin ed. Contemporary Developments in Indonesian Islam: Explaining the